Scientific and economic support for construction development in the countryside of Ukraine - Azhaman, Iryna; Nataliya, Telichko (International Journal of Engineering and Technology, 2018)
The article is devoted to the concept-categorical apparatus concerning scientific and economic support of industrial and civil construction development in the countryside ofUkraine. The author defines concepts of scientific and economic provision, development, countryside, construction. On the basis of generalization of theoretical studiesâ€™ results, the author's interpretation of the essence of construction development in the countryside is provided, where the latter is considered as a dynamic process, a movement to acquisition of qualitatively new parameters and properties by industrial and civil construction in rural areas, which will be carried out in accordance with achievements of scientific and technological progress in the field of construction and will promote: satisfaction of individual and social needs of rural subjects, sustainable development of rural areas, forming positive image of rural areas and the country in conditions of globalization and integration. Subjects and objects of construction activity are defined. Types of construction in the countryside ofUkraineare highlighted.Â Â